THU0760-HPR Patient advice line - the potential clinical and financial benefits to a rheumatology department. (15th June 2017) - Mason, A; Beevor, C; Ledingham, J
Abstract : Background: EULAR recommendation 3 for the role of the nurse in the management of chronic inflammatory arthritis states that patients should have access to nurse-led telephone services to enhance continuity of care and to provide ongoing support (1). In the UK quality standard 6 of the National Institute for Health and Care Excellence guidelines for the care of rheumatoid arthritis (RA) recommends that people with RA and disease flares, or possible drug related side effects should receive advice within 1 working day of contacting the rheumatology service. In 2016 audit data from England and Wales show that 96% of trusts report being able to provide patients with a telephone advice line but no further detail on these services was available (2). Objectives: Data from our patient advice line were collected over a 6 month period. The objective was to understand who was using the helpline, the speed of our response, how much of the workload could be managed by nursing staff and the clinical and financial impact. Methods: All patient calls made to our patient helpline were recorded and data were collected prospectively on patient demographics, disease, purpose of call, response time and the cost and revenue produced. Patient feedback was collected via a questionnaire. Data were collected from April 2016 to November 2016. Results: 150 patient calls were responded to. 108 calls were from females and were 42 from males. The majority of patients had RA (75/150). Other conditions are displayed in the graph below. The majority of calls were regarding a flare of their condition or medication queries (79/180 and 39/180 respectively) with some patients calling for more than one reason. 83% of calls were answered within 24 hours. A clinical nurse specialist is available to respond to calls over weekends. Income generated from responding to calls by the department was £ 1900 per month. Expenditure was £ 1650 per month. Patient satisfaction was high with 130/150 stating the main reason for the call was answered to their satisfaction (7 stating no, 13 not stated). Conclusions: Our advice line gives patients easy access to specialist advice. Patient satisfaction is high. Responses are timely and fast. Multiple concerns are commonly addressed, such as advice regarding flare of disease and medication queries. This service will be References: Van Eijk-Hustings et al. EULAR recommendations fo the role of the nurse in the management of chronic inflammatory arthritis. Ann Rheum Dis 2012;71:13–19. BSR Rheumatoid and Early Arthritis 2nd Annual Report 2016. Available http://www.hqip.org.uk/resources/rheumatoid-and-early-inflammatory-arthritis-2016/ . Disclosure of Interest: None declared